Zakat Produktif Dalam Meningkatkan Kualitas Pendidikan Mustahiq Ditinjau Dari Standar Penilaian Pendidikan, Standar Proses, dan Standar Sarana Prasana (Studi Kasus LAZ Inisiatif Zakat Indonesia Cabang Jawa Timur) - Dimas Rizky Syah Putra; Tika Widiastuti (Universitas Airlangga, 2019)
Zakat productive is the utilization of zakat through productive management and empowerment processes, which in practice is carried out by channeling capital into mustahiq which is then managed to fulfill their welfare in the future. This research aims to analyze the role of productive zakat managed by LAZ IZI which has a role in improving the quality of mustahiq education in the Surabaya City. The results of this research indicate that productive zakat funds managed by LAZ IZI play a role in educational assessment standards in the form of increasing GPA for students and report cards for students, then in standard processes in the form of increases in study hours, training and activeness of intra and extra organizations, and the role in standard facilities and infrastructures in the form of increasing learning needs equipment such as notebooks, textbooks, stationery, and other facilities.Keywords : Productive Zakat, Mustahiq, Education QualityREFFERENCESAdinugroho, Achmad Setio, Nuraini, Dwi dan Riyanto, Dwi. 2018. Statistik Zakat Nasional 2017. Badan Amil Zakat Nasional.Asnaini. 2008. Zakat Produktif Dalam Perspektif Hukum Islam. Yogyakarta: Pustaka Pelajar.https://izi.or.id/https://kbbi.web.id/didikhttps://www.bps.go.id/Nidityo, Herwindo Ghora & Laila, Nisful. 2014. Zakat Produktif Untuk Meningkatkan Kinerja Produksi, Motivasi Dan Religiusitas Mustahiq. Surabaya.Ryandono, Muhammad Nafik Hadi. 2008. EkonomiZiswaq(Zakat, Infaq, Shadaqah, dan Waqaf). Surabaya: IFDI dan Cenforis.Sartika, Mila. 2008. Pengaruh Pendayagunaan Zakat Produktif Terhadap Pemberdayaan Mustahiq Pada Laz Yayasan Solo Peduli Surakarta. vol.ii no. 1, juni 2008.Shihab, Muhammad Quraish.1999. Membumikan Al-Quran. Bandung : Mizan.Sugiyono. 2015. Memahami Penelitian Kualitatif. Bandung: Alfabeta.Widiastuti, Tika. Mawardi, Imron. 2016. Optimalisasi Pengelolaan Dana Zakat di Lembaga Zakat daerah : Pendekatan SWOT (strength, weakness, opportunity, threat) Analysys. Surabaya. Politeknik Negeri Banjarmasin.Yin, Robert. K. 2009. Studi Kasus; Desain dan Metode. Jakarta. Raja Grafindo Persada.Zaenal, Muhammad Hasbi. 2017. Indonesia Zakat Outlook 2018. Badan Amil Zakat Nasional.